Effect of harvesting at different stages of growth and long term storage on phenolics in sorghum stover - Khazaal, K.; Mueller-Harvey, I.; McAllan, A.B.; Osafo, E.L.K.; Owen, E.; Said, A.N. (British Society of Animal Production, 1993)
Studies changes in the concentrations and composition of phenolic compounds in component parts of different sorghum varieties harvested at different growth stages and also after long time storage.